Pengaruh Work-Life Balance dan Kepemimpinan Terhadap Produktivitas Kerja Pada Karyawan CV Kodoc Collection - Ardiansyah, Rendi; Musharianto, Adi (Innovative: Journal Of Social Science Research, 2025)
This study examines the effects of job-related stress and leadership on employee productivity at CV Kodoc Collection. The study shows that employee productivity is positively correlated with their job-related well-being, with a significant contribution of about 32.6% to this increase. In addition, effective leadership sustains important goals, contributing about 46.7% to productivity growth. These findings indicate that both factors are essential to creating a productive work environment. This study highlights the need for companies to prioritize employee well-being and use effective leadership strategies to improve employee productivity. This is consistent with previous studies that show that a positive balance between personal and professional life affects productivity. The results of the study indicate that organizational reforms that focus on employee well-being and leadership development can result in better productivity.